Experiencing earthquake in the first trimester of the fetal life increases subsequent diabetes risk in the adulthood: a cross-sectional study - Li, Na (Reprod Biol Endocrinol, 2020)
OBJECTIVE: To investigate the long-term effect of prenatal exposure to earthquake stress on diabetes risk in the adulthood. METHODS: This study included employees of Tangshan Kailuan Mining Group between July 29, 1976 and April 28, 1977. The exposure group included subjects who experienced the Tangshan Earthquake during their prenatal period and who had lived in Tangshan since birth. The non-exposure group included subjects who were born 1–1.9 years after the earthquake and who had lived in Tangshan since birth. A questionnaire was designed that included sociodemographic information, conditions during pregnancy, and earthquake experience. Anthropometric measurements including height and weight, body mass index (BMI), waist circumference were made. Fasting plasma glucose (FPG) and lipid profiles were also determined. RESULTS: Totally 947 subjects were included with 397 subjects in the exposed group and 550 subjects in the non-exposed group. The diabetes rate is significant different in these four groups(χ(2) =8.045, P = 0.045). Moreover, 11.8, 7.5 and 8.0% of the subjects who were exposed to earthquake in the 1st, 2nd, and 3rd trimester of pregnancy had diabetes. 5.1% of the subjects had diabetes in non-exposure group. Our multivariate analysis showed that 1st trimester (OR 2.481, 95%CI 1.02, 6.034; P = 0.045) and loss of family members during earthquake (OR 2.452, 95%CI 1.293, 4.653; P = 0.006) were associated with significantly increased risk of diabetes. CONCLUSIONS: Exposure to earthquake during the first trimester of pregnancy and experience of family member loss in the earthquake significantly increased the subsequent risk of diabetes in the middle age (36–39 years of age). Our data suggest that earthquake experience in the early pregnancy has a longer-term effect on diabetes risk during adulthood.